Hubungan Lama Pemakaian KB Suntik dengan Gangguan Siklus Menstruasi pada Akseptor KB Suntik di PMB Neneng Mahfuzah Banjarmasin - Adinda Raudita; Anik Purwati (Pusat Riset dan Inovasi Nasional, 2025)
Background: One of the most popular contraceptives in Indonesia is injectable contraception. However, each contraceptive method certainly has its own side effects, hormonal methods such as injections generally have side effects in the form of menstrual disorders, weight changes, dizziness or headaches and an increase in blood pressure. The purpose of this study is to determine the long-term relationship between the use of injectable birth control and menstrual cycle disorders in birth control acceptors at PMB Neneng Mahfuzah Banjarmasin in 2024. This study uses a quantitative descriptive method with a cross sectional approach with a sample of 85 people with details of 48 respondents for 1-month injectable birth control and 37 respondents for 3-month injectable birth control. The results obtained from the bivariate analysis of the chisquare statistical test showed that the value of p = 0.010 > α = 0.05. The conclusion is that there is a relationship between the length of use of birth control and menstrual cycle disruption in injectable birth control acceptors at PMB Neneng Mahfuzah Banjarmasin in 2024. Advice is expected that health workers can provide KIE about the side effects of using Injectable Family Planning, one of which is menstrual cycle disruption. So that the acceptor can choose wisely the contraceptive method he wants to use.